LDL Level in Ischaemic Stroke Patients at Dr. Soetomo General Hospital Surabaya - Mayori Rachmawati; Paulus Sugianto; Rr. Indrayuni Lukitra Wardhani (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Stroke is one of the top killers amongst the non-infectious diseases. Ischemic stroke dominates the rate by 87.0% amongst all type of strokes. One of the risk factors for stroke ischemic stroke is atherosclerosis which caused by lipid build-up in the arteries.Methods: This research is a retrospective study on secondary data. Admitted Ischaemic stroke patients. Lipid profile, and Barthel Index were collected from medical record and presented descriptively.Results: Of the 248 patients, 144 (58.1%) were men, mean age was 59.33. 61.7% ischemic stroke patients have their LDL level elevated, 59.7% HDL decreased, 39.1% total cholesterol elevated, and 33.9% TG elevated. This study also observe the dependency based on Barthel Index of the admitted stroke patients. 75% percents amongst subjects were categorized as “total dependece” are having their LDL level elevated.Conclusion: Most of stroke patients have elevated LDL and HDL while the TG and total cholesterol are mostly optimized. Stroke patients whose admitted with “total dependence” most likely to have elevated LDL in this study.